Development of a Web-Based Alumni Information System at Universitas Hindu Indonesia - Sanjaya, Kadek Oky; Jaya, I Kadek Noppi Adi; Arta, I Made Esa Juana; Maharani, Ni Made Sintha (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The development of an Alumni Information System based on a Website is an effective solution in managing information and data regarding an institution's alumni. Issues related to non-systemic and manual information dissemination, as well as challenges in gathering alumni data, are expected to be resolved by this system. It is anticipated that this system will facilitate alumni in connecting and interacting. The aim of this research is to develop an effective and efficient alumni information system to enhance alumni engagement and participation in institutional activities. The research follows a waterfall model involving various stages, starting from needs analysis, design, implementation, testing, to maintenance. The developed alumni information system includes features such as alumni profiles, current news and information, job vacancies, and alumni activities. This system is implemented in the form of a website using the CodeIgniter framework. Testing results using black box testing indicate that this system effectively manages various data and information crucial for alumni. Alumni using this system can easily access and update their profile information, as well as connect with fellow alumni and the institution. For future research, it is hoped that a more flexible information system can be developed, perhaps in the form of a mobile-based application.